HEALING POWER OF FLOWERS : discover the secret language of the flowers you love. - BOWEN, CLAIRE (EBURY PRESS, 2021)
Live life in full bloom. This beautiful book features your favourite flowers grouped by their purpose - for love, for joy, for luck, for calm, to console, and to celebrate. Discover their traditional meanings, holistic benefits, and when flowers are in season so that they can be sourced locally with a minimal carbon footprint. By creating thoughtful personal bouquets or choosing a flower for its meaning, its natural energy, or holistic property, you can bring the benefits of the natural world back into your home, your workplace, and into the lives of loved ones. Find out why you should give Foxgloves to celebrate a new job, Lilacs for joy, or Chrysanthemums for luck, and become fluent in the secret language of flowers.